Konstruksi Konsep Penyembuhan dalam Al-Qur'an: (Studi Interpretatif Ayat-Ayat Tentang Syifa’) - Tazkia Nur Fateha; Syafiin Mansur (Reflection : Islamic Education Journal, 2025)
In recent decades, the concept of healing has developed rapidly, no longer limited to the medical and psychological fields, but also includes spiritual and religious aspects. In the Islamic view, the Qur'an contains the concept of healing through the term syifa', which means healing or medicine for illnesses, both physical and spiritual. This study aims to formulate an understanding of healing in the perspective of the Qur'an by studying verses containing the word syifa', such as QS. Yunus: 57, An-Nahl: 69, and Ash-Syu'ara: 80. The method used is qualitative research based on literature studies by examining various classical and modern interpretations to understand the meaning, context, and values ​​contained therein. The results of the study show that although healing and syifa' are both related to the healing process, they have different foundations. Healing emphasizes more on psychological processes and human experiences, while syifa' is rooted in the teachings of monotheism and describes God as al-Shāfī. The Healer. In the Qur'an, healing does not only mean freedom from physical illness, but also includes inner peace and spiritual closeness to God. Classical interpretations focus more on moral and spiritual aspects, while contemporary interpretations develop these concepts into psychospiritual healing concepts relevant to modern life.